The history of the formation and development of the institution of diplomatic immunities and privileges in the United States - A. A. Nagieva; A. E. Samadova (Правоприменение, 2023)
The subject of study. Throughout the historical period of the development of diplomatic law, an institution of immunities and privileges was formed, the content and scope of which were determined by the level of diplomatic relations between states and the development of public administration.The rules of national law also have a significant impact on the procedure for exercising dip- lomatic immunities and privileges. Many states have adopted legal acts regulating the foun- dations of the diplomatic service. For example, in the United States, after joining the Vienna Convention on Diplomatic Relations of 1961, the Law on Diplomatic Relations of 1978 was adopted, based on the rules of this Convention.The article examines the history and development of diplomatic immunities and privileges, the formation of the US diplomatic service and the content of current national laws in the US. The purpose of the study is the identification of problems in the practice of implementing diplomatic immunities and substantiate the hypothesis that it is necessary to develop the legislation on diplomatic immunities and the diplomatic service in the United States.The methodology of the study. The methodology of the study includes general scientific methods (analysis, synthesis, description, systematization) and special scientific methods (formal legal and comparative legal methods). In addition to this, historical method was also applicable.The main results. Based on the results of the study, were disclosed significant discrepancies between the national legal regulation of the US diplomatic service and the rules of interna- tional law, which leads to massive violations of diplomatic immunities and privileges by the US authorities.Conclusions. Diplomatic immunity is a guarantor of the effective operation of foreign rela- tions bodies on the territory of the host state, however, in practice, there are often cases of their violation by the authorities of the host state and cases of abuse of diplomatic im- munities and privileges by their carriers. The granting of a special legal status, personal in- violability and other privileges and immunities is in no way equated to absolute impunity for employees of foreign relations bodies in case they commit illegal acts.